Femininities, Masculinities, Sexualities : Freud and Beyond - Chodorow, Nancy J. (Book collections on Project MUSE., 2014)
Nancy J. Chodorow takes her fellow psychoanalysts to task for their monolithic and pathologizing accounts of deviant gender and sexuality. Drawing from her own clinical experience, the work of Freud, and a close reading of psychoanalytic texts, Chodorow argues that psychoanalysis has yet to disentangle male dominance from heterosexuality. Further, she demonstrates the paucity of psychoanalytics understanding of heterosexuality and the problematic polarizing of normal and abnormal sexualities. By returning to Freud and interpreting psychoanalysis through clinical eyes, Chodorow contends that.